Anesthesia Management in Patient with Uncorrected Double Outlet Right Ventricle Underwent Cesarean Section: Serial Case Report - Ilham Fadlilah; Ruddi Hartono; Isngadi Isngadi (Journal of Anaesthesia and Pain, 2022)
Background: Double outlet right ventricle (DORV) is a rare cardiac condition in which the heart demonstrates single ventricle physiology. Pregnancy complicates cyanotic heart disease as the decrease in systemic vascular resistance (SVR) worsens the right-to-left shunt. The effect worsens by neuraxial anesthesia for cesarean delivery. Anesthesia for these patients needs understanding for the physiology of DORV in order to maintain stable hemodynamics. Heart defect still become non obstetric main factor causing morbidity and mortality in pregnant woman.Case: We present three case of parturients with DORV scheduled for cesarean section. Elective caesarean section was scheduled using spinal anesthesia hyperbaric bupivacain combined with fentanyl.  Hemodynamic during operation was stable.Conclusion: Low dose spinal anesthesia performed in this patient did not cause hypotension and minimal hemodynamic changes because the intensity of the sympathetic block was lower.